THE EFFECT OF AUDIT PARTNER BUSYNESS, PUBLIC ACCOUNTING FIRM REPUTATION, AND AUDITOR OPINION ON AUDIT DELAY IN CONSUMER CYCLICAL SECTOR COMPANIES LISTED ON THE IDX - Irnawati, Irnawati; Gurendrawati, Etty; Sasmi, Aji Ahmadi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine influence of audit partner busyness, public accounting firm reputation and auditor opinion on audit delay. The population in this study were companies in the Consumer Cyclicals Sector listed on the Indonesia Stock Exchange in 2019-2021. The number of samples in this study were 67 companies. The sampling technique uses purposive sampling method and produced 267 observations. The research method used is quantitative with secondary data sources. The method of data analysis uses multiple linear regression analysis with SPSS 16. The results of this study provide empirical evidence that partially audit partner busyness and public accounting firm reputation do not have a significant effect on audit quality. Meanwhile, auditor opinion has a negative significant effect on audit delay. Simultaneously the audit partner busyness, public accounting firm reputation and auditor opinon have a significant effect on audit delay